The influence of introduced forest management practices on transformative social learning in a selected social-ecological forest community : a case of PFM and REDD projects at Pugu and Kazimzumbwi Forest Reserves in Tanzania - Ferdinand, Victoria Ugulumu (Rhodes University, Faculty of Education, Department of Education, 2016)
This research investigates the influence of introduced forest management approaches on transformative social learning in the community surrounding the Pugu and Kazimzumbwi forest reserves in Tanzania from 2000 to 2015. The term transformative social learning reflects an understanding of learning processes that emerge through conscious changes in the perspectives of individuals or communities while interacting with forest management practices. The investigation explores the learning (if any) that occurred in the community and how and why the learning occurred. It also explores whether the learning was social and transformative and examines the conditions that enable or constrain transformative social learning at the Pugu and Kazimzumbwi community. Thus, the three concepts of social learning, transformative learning, and social practices are central to the research. Participatory Forest Management (PFM) emerged globally in the early 1980s to mobilise rural capabilities and resources in development and environmental stewardship. The Pugu and Kazimzumbwi community was introduced to Participatory Forest Management (PFM) projects by the late 1990s. The recent global focus on empowering communities around forests has drawn attention towards transformational adaptation to climate change impacts and building resilience capacities. As a result, in 2011 the Pugu and Kazimzumbwi community started working with a project for Reduction of Emissions through Deforestation and forest Degradation (REDD), which forms a key focus in this study as the most recently introduced PFM with embedded social learning assumptions. This research is designed and conducted as a qualitative case study. The research seeks to study the complex object of socially and contextually constructed learning through a systemic exploration of learning,using semi-structured interviews, focus group discussions, analysis of documents and archival records as well as observations and a reflexive workshop. Supportive information throughfield notes and audio voice and video recording was also generated. A contextual profile of the research site was conducted in March 2012, prior to the actual data collection in 2013 and 2014. Field explorations during the contextual profile helped to describe the research site and promote initial understanding of the context. During data collection, field inquiries based on interactive relationships between a researcher and participants stimulated practice memories and people's living experiences with forestry and the introduced PFM projects under examination. Analysis of data employed analytical modes of induction, abduction and retroduction. Thick descriptions of learning obtained from fieldi based interactionswere produced before re-contextualising data through theoretical lenses. The research employed realist social theory by Archer (1995), under-laboured by critical realism, and practice theory advanced by Schatzki (2012) and Kemmis et al. (2014). The research process as a whole was underlaboured by the layered ontology of critical realism which proposes emergence of phenomena in open systems as shaped by interacting mechanisms which in this study were both material / ecological and social /political /economic /cultural. And more...
Keywords: Forest management -- Tanzania; Forest reserves -- Tanzania; Transformative learning; Social ecology